Regulation of active genome integrity and expression by Rad26p - Malik, Shivani (Nucleus, 2014)
Rad26p is a SWI/SNF-like ATPase in yeast, and is conserved among eukaryotes. Both Rad26p and its human homolog CSB (Cockayne syndrome group B) are involved in regulation of chromatin structure, transcription and DNA repair.  Thus, mutations or malfunctions of these proteins have significant effects on cellular functions. Mutations in CSB are associated with Cockayne syndrome (CS) that is characterized by heterogeneous pathologies such as mental and physical retardation, sun sensitivity, premature aging, muscular and skeletal abnormalities, and progressive decline in neurological and cognitive functions. Therefore, many research groups focused their studies to understand the mechanisms of Rad26p/CSB functions to illuminate the molecular bases of CS. These studies have provided significant functional and mechanistic insights of Rad26p/CSB in regulation of gene expression and genome integrity as described here.